Hypothesis testing sustained declines in COVID-19 intensity - Scott Ganz (American Enterprise Institute (AEI), 2020)
Gating indicators recommended by CDC for phased reopening following COVID-19 shutdowns include "sustained decreases" or a "downward trajectory...over a 14-day period" in public health statistics.
Keywords: A; 330; Coronavirus; economics; public health; Economic policy responses for reopening the country